2015
DOI: 10.1089/scd.2014.0227
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Culture and FGF Signaling Drive Differentiation of Murine Pluripotent Cells to Distal Lung Epithelial Cells

Abstract: Reciprocal signaling between the lung mesenchyme and epithelium is crucial for differentiation and branching morphogenesis. We hypothesized that the combination of signaling pathways comprising early epithelialmesenchymal interactions and a 3D spatial environment are necessary for an efficient induction of embryonic and induced pluripotent stem cells (ESCs and iPSCs) into a lung cell phenotype with hallmarks of the distal niche. Aggregating early, but not late, embryonic lung mesenchyme with endoderm-induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…FGF9 is also produced at higher levels by PSs, in combination with TGFβ2. These factors play key roles in regulating lung development [], and the powerful combination of FGF signaling and 3D culture on the differentiation efficiency of embryonic stem cells into distal epithelial cells has recently been reported []. Interestingly, PSs and PDCs secrete HGF in similar amounts able to sustain clonal self‐renewal and epithelial colony formation, mediating mesenchymal support [] and epithelial/endothelial crosstalk [].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF9 is also produced at higher levels by PSs, in combination with TGFβ2. These factors play key roles in regulating lung development [], and the powerful combination of FGF signaling and 3D culture on the differentiation efficiency of embryonic stem cells into distal epithelial cells has recently been reported []. Interestingly, PSs and PDCs secrete HGF in similar amounts able to sustain clonal self‐renewal and epithelial colony formation, mediating mesenchymal support [] and epithelial/endothelial crosstalk [].…”
Section: Discussionmentioning
confidence: 99%
“…Phenotype control of isolated cells represents a delicate task to manage in vitro, for both basic and translational research. Multiple stimuli play synergic roles on lung stem cell niches, modulating proliferation, commitment, epithelial‐to‐mesenchymal (EMT) or the opposite mesenchymal‐to‐epithelial transition, and crosstalk with stroma [, , ]. The extracellular matrix has a central influence as well.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the differentiation of human ESCs and iPS cells into pulmonary epithelium has been challenging. Several research groups have reported the successful differentiation into various lung epithelial cell types using a variety of protocols (Wang et al, ; Van Haute et al, ; Ameri et al, ; Green et al, ; Kadzik and Morrisey, ; Longmire et al, ; Mou et al, ; Ghaedi et al, ; Firth et al, ; Fox et al, ), which are based on sequentially exposing pluripotent stem cells to growth factors in a way that mimics the steps of lung endoderm development in vivo. However, the efficiency of this process is still subpar and usually generates a mixed population of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Slides were washed thoroughly with 1ϫ PBS, and primary antibody was detected by using corresponding secondary antibodies diluted in blocking buffer for 1 h at room temperature. Nuclei were stained with DAPI dye followed by mounting using ProLong Gold anti-fade reagent (Molecular Probes, Carlsbad, CA) Fluorescent images were captured with a Leica CTRMIC 6000 confocal microscope in conjunction with a Hamamatsu C910013 spinning-disk camera (Leica Microsystems, Concord, ON, Canada) (13). Laser intensity and detector sensitivity settings remained constant for all image acquisitions within a respective experiment.…”
Section: Methodsmentioning
confidence: 99%